Theoretical and Methodological Basis for Studying the Needs and Advantages in Youth Activities - Farrukh Yuldashev (Indonesian Journal of Cultural and Community Development, 2023)
This article studies the harmony of needs and interests in the activities of young people in the information society, revealing the conceptual foundations and socio-philosophical aspects of the harmony of needs and interests, conflicts in meeting the needs and interests of young people in the space of information struggle, the commonality of needs and interests in the process modernization of society and building a civil society on the basis of means of provision.